The seismic performance of stone masonry buildings in Faial island and the relevance of implementing effective seismic strengthening policies. (15th June 2017) - Maio, Rui; Estêvão, João M.C.; Ferreira, Tiago M.; Vicente, Romeu
Highlights: Seismic vulnerability assessment of existing stone masonry buildings. Pushover analyses are performed adopting the FME approach. Different performance-based procedures are used to verify the seismic safety. The influence of traditional strengthening solutions is analysed. Analytical fragility curves are derived. Abstract: Enhancing the seismic performance of traditional stone masonry buildings is considered a crucial measure towards the preservation and safeguarding of our built heritage, particularly in seismic prone areas such as the Azores archipelago, in Portugal. In this context, the present paper is focused on the seismic vulnerability assessment of two traditional stone masonry building located in the Faial Island, taken as typologically representative of the rural Azorean building stock. The case study buildings were modelled based on the equivalent frame model approach and non-linear static (pushover) analyses were performed to assess their seismic performance. Firstly, results were compared in terms of capacity curves, and secondly, two different seismic performance-based assessment methods (N2 and CSM) were used to determine the respective performance points and assess the seismic safety of both structures. The seismic demand was defined by a set of real ground motion records, which the authors assumed as representative of the 1998 Azores earthquake, both in terms of magnitude and epicentral distance. Additionally, a set of traditional retrofitting solutions were implemented to the original models in order to analyse and compare their influence over the building's global seismic performance. These solutions were adopted in the aftermath of the 1980 and 1998 Azores earthquakes by different design offices and engineering consultants, based on the designing recommendations specifically prepared by the Regional Laboratory of Civil Engineering (LREC) under the scope of the Faial rehabilitation process. Finally, fragility curves were derived based on the spectral response approach, and the results were critically discussed.